Assessing Efficiency of Preferential Treatment from Resident Position - D. A. Antonova (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
The article deals with the research analyzing adverse factors influencing the efficiency of preferential treatment functioning in the Far-East Federal Area. To build a complex assessment of factors hindering the development of business and affecting the demand for preferential treatment on the part of investors a survey of effective residents of preferential treatment zones was conducted. The author came to practical conclusions, which can be used for further upgrading of statutory enactments necessary to establish and regulate preferential treatment in the Far-East Federal Area. The research is based on statistic data of the Ministry on Developing the Far East and the Arctic and the limited company ‘The Corporation of Developing the Far East and the Arctic’. The findings of the research can be used by federal authorities of the Russian Federation, bodies of power in entities of the Russian Federation and controlling companies in order to improve investment climate on the territory of the Far-East Federal Area.